Modified MALDI MS fatty acid profiling for bacterial identification. (27th June 2013) - Voorhees, Kent J.; Jensen, Kirk R.; McAlpin, Casey R.; Rees, Jon C.; Cody, Robert; Ubukata, Masaaki; Cox, Christopher R.
<x xml:space="preserve">Abstract</x> Bacterial fatty acid profiling is a well‐established technique for bacterial identification. Ten bacteria were analyzed using both positive‐ and negative‐ion modes with a modified matrix‐assisted laser desorption ionization mass spectrometry (MALDI MS) approach using CaO as a matrix replacement (metal oxide laser ionization MS (MOLI MS)). The results show that reproducible lipid cleavage similar to thermal in situ tetramethyl ammonium hydroxide saponification/derivatization had occurred. Principal component analysis showed that replicates from each organism grouped in a unique space. Cross validation (CV) of spectra from both ionization modes resulted in greater than 94% validation of the data. When CV results were compared for the two ionization modes, negative‐ion data produced a superior outcome. MOLI MS provides clinicians a rapid, reproducible and cost‐effective bacterial diagnostic tool. Copyright © 2013 John Wiley & Sons, Ltd.